1993
DOI: 10.1111/j.1471-0528.1993.tb15142.x
|View full text |Cite
|
Sign up to set email alerts
|

Infertility treatment: from cookery to science. The epidemiology of randomised controlled trials

Abstract: Objectives To review the epidemiology of published randomised controlled trials in infertility treatment over the last 25 years, with special emphasis on the number and quality of trials. Design Computer literature review by MEDLINE backed up by a manual search of 41 journals. Each trial was classified according to the methodology described and quality criteria. The results were recorded in a computer database. Odds ratios (OR) and confidence intervals (CI) were calculated where the data were suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 291 publications
0
22
0
2
Order By: Relevance
“…177 The updating identified only an abstract by Martin et al (2004) in which they examined the impact of including duplicate publications in a metaanalysis of off-pump versus on-pump coronary artery bypass surgery. 178 Trials were classified as covert duplicates when there was no citation of the original publication and non-covert duplicates when the publication declared the duplication or cited the original publication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…177 The updating identified only an abstract by Martin et al (2004) in which they examined the impact of including duplicate publications in a metaanalysis of off-pump versus on-pump coronary artery bypass surgery. 178 Trials were classified as covert duplicates when there was no citation of the original publication and non-covert duplicates when the publication declared the duplication or cited the original publication.…”
mentioning
confidence: 99%
“…22 Vandekerckhove et al (1993) identified a review of RCTs of infertility treatment and found that 'six studies with a significant result (but none with a non-significant result) were reported in four publications from the same institution'. 177 The updating identified only an abstract by Martin et al (2004) in which they examined the impact of including duplicate publications in a metaanalysis of off-pump versus on-pump coronary artery bypass surgery.…”
mentioning
confidence: 99%
“…The creation of registers of randomised controlled trials to assist the preparation and maintenance of systematic reviews affords an opportunity to assess the quality and content of evaluative research within welldefined sampling frames (Adams & Gelder, 1994) When this large survey was planned there were examples of surveys of randomised trials within specific journals (Ahmed et al, 1998;Lent & Langenbach, 1996;Fahey et al, 1995;Doll, 1998) but research into the quality and content of trials within specific health care specialities was, and is, less common (Chalmers, 1986;Vandekerckhove et al, 1993;Silagy, 1993;Chalmers et al, 1986;Nicolucci et al, 1989;Cheng et al, 2000).checked for duplicates before two trained selectors highlighted studies that were clearly or possibly relevant. Full copies of these reports were then acquired (6000), re-inspected and, if meeting the inclusion criteria, added to the final register.…”
Section: The Pastmentioning
confidence: 99%
“…(Vandekerckhove et al, 1993). Instead, observational data (often from large, insurance claims databases) have been used in 'outcomes research'.…”
Section: Thefuturementioning
confidence: 99%
“…Trois 6tudes comparant les r6sultats avec ceux obtenus avec un placebo montrent que ce traitement est inefficace dans ces conditions (Tableau 1). Dans la m6ta-analyse r6alis6e par Vandekerkhove et al [56] ou O'Donovan et al [36], les r4sultats combin6s montrent l'absence de diff6rence entre les patients trait6s et ceux ayant r%u un placebo, en terme de grossesses obtenues.…”
Section: Les Inhibiteurs De La Prolactineunclassified